The practice reality of ward based midwifery care: An exploration of aspirations and restrictions. Issue 4 (July 2020) - Lewis, Lucy; Barnes, Courtney; Roberts, Lauren; McLeod, Laura; Elliott, Angela; Hauck, Yvonne L.
Abstract: Background: This paper reports on research that explores the experience of the ward based midwife, as research suggests workplace balance is problematic. Aim: To explore the processes and practices around ward based clinical engagement and its impact in an Australian public tertiary obstetric unit. Methods: A qualitative descriptive study was undertaken. Focus groups were used to gather data. Groups were audio recorded and transcribed verbatim. Thematic analysis was continued until data saturation was achieved. Findings: Seven focus groups involving 40 midwives were conducted. Midwives' voices suggested tensions arose when their aspirations around core professional values and camaraderie were compromised by the practice realism of the ward. Furthermore, they described frustration with imposed restrictions which governed their working environment. These occurred outside the ward, had a direct impact on how it functioned, and were perceived to be out of the midwives' control. Midwives experiencing emotional distress revealed they were carrying a burden. Two burdens were described: disengagement and what have I missed? Conclusion: Thought must be given to how the art of midwifery is practiced on the ward. Ignoring the growing body of literature on this subject will be problematic for both midwives and women, as midwives will be disempowered to foster women's capabilities through tailored, supportive and respectful care.